Determinan Manipulasi Akrual Dalam Pelaporan Keuangan Pemerintah Daerah - Handayani; Darwanis; Syukriy Abdullah (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to determine the effects of government size, fiscal capacity, fiscal distress, and legislature size on accrual manipulation in local government financial reporting. The study was conducted on 23 local governments in Aceh with data analysis using multiple linear regressions. The data is extracted from audited financial reports of the local governments for the period 2016-2020. This study uses the Modified Jones Model to measure the manipulation of accruals. The results show that the government size and fiscal distress have a negative effect on accrual manipulation, legislature size has a positive effect on accrual manipulation, and fiscal capacity have no effect on accrual manipulation. These results indicate that the accrual manipulation in financial reporting can occur due to discretionary policies carried out by local government officials with the aim of making their financial performance look good.